Sosialisasi Kesehatan Reproduksi Pada Remaja Di Madrasah Tsanawiyah Nurul Islam Sekarbela Kota Mataram - Putri Yayu; Jumriani; Nurbaety (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
Reproductive health is a psychological, social and physical healthy condition, which is related to the function, process and reproductive system, for both men and women so that they can be responsible for maintaining and protecting the reproductive organs. Adolescents are at risk of experiencing reproductive health and mental health problems. However, until now teenagers' knowledge and experience regarding this matter is still very minimal. So far, they understand reproductive health to be limited to physical matters, such as puberty and menstruation. Meanwhile, the sources of reproductive health (kespro) and mental health information that teenagers have accessed through digital media are not yet inclusive and are not supported by professional assistance. Socialization about reproductive health in adolescents aims to prevent the occurrence of sexually transmitted infections in adolescents due to free sex and other negative relationships using methods, namely interactive lectures and guided discussions. This community service activity was carried out in June 2024 at MTs Nurul Islam Sekarbela, Mataram City, which was attended by 27 students, 2 teachers, 3 lecturers with the results of providing material on adolescent reproductive health, which is one of the effective methods in improving adolescent knowledge regarding reproductive health. Students were very enthusiastic in participating in the activities as evidenced by the two-way discussions and the teenagers were able to answer the questions given well and precisely.